Names of Persons as a Central Component of Language Life of Society - Ibraximova D. T. (Researchparks Publishing, 2022)
Anthroponymic systems of languages reflect the history and culture, worldview and values of the people. Therefore, the study of this layer of linguistic vocabulary should play an important role in ethno linguistics, one of the directions of which is to reveal the image of the people in the language. On the other hand, the study of personal names is also of practical importance: knowledge of the development trends of the personal name system helps to influence these processes consciously and scientifically based in the context of language policy.